PROGRAM KALIMANTAN FORESTS AND CLIMATE PARTNERSHIP DALAM MENGURANGI EMISI DEFORESTASI DAN DEGRADASI HUTAN (STUDI PADA KEGIATAN PERSEMAIAN DESA SEI AHAS) - Mochammad Doddy Syahirul Alam (Jurnal Universitas Paramadina, 2013)
AbstractREDD (Reducing Emissions from Deforestation and Forest Degradation) belonged to the main agenda of the countries that have committed to decreasing the emissions. Indonesia as one the country has big role to decreasing the emissions that have large resources especially wetland and forestry. The REDD activity that was held in Indonesia has main location in central Kalimantan. The project is called Kalimantan Forest Climate Partnership. It was held in 7 villages in Kapuas district. The main activity called demontration activity which the real activity is nursery. The nursery activity is the important thing activity, but there are some aspect that was raised like; social structure, performance of the committe, and communication. First, the problem in the field about social structure is the domination of the local the government. The local government almost influences the all programs. Second, the gender performance is still in the low participation. The process of decision making is still dominated by the man. But actually the gender partipation is good enough for maintaining the nursery. Third, the communication process show the some problems like unvalid information, overlapping on job description, complain management that didn’t work.Keyword : REDD, KFCP, Nursery